2017
DOI: 10.18632/oncotarget.21218
|View full text |Cite
|
Sign up to set email alerts
|

Involment of RAS/ERK1/2 signaling and MEF2C in miR-155-3p inhibition-triggered cardiomyocyte differentiation of embryonic stem cell

Abstract: MicroRNAs (miRNAs) are short, noncoding RNAs that regulate post-transcriptional gene expression by targeting messenger RNAs (mRNAs) for cleavage or translational repression. Growing evidence indicates that miR-155 expression changes with the development of heart and plays an important role in heart physiopathology. However, the role of miR-155 in cardiac cells differentiation is unclear. Using the well-established embryonic stem cell (ESC), we demonstrated that miR-155-3p expression was down-regulated during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Systemic administration has been proven to mitigate dysfunction and improve survival by targeting JNK . Nevertheless, miR-155 knockdown triggers apoptosis via induced liposaccharides [ 45 , 55 , 56 ]. In concert with miR-155, miR-146 downregulates expression of IRAK1 and TRAF6 , which are upstream activators of NF-κβ [ 5 ].…”
Section: Mirnas In Cardiomyocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic administration has been proven to mitigate dysfunction and improve survival by targeting JNK . Nevertheless, miR-155 knockdown triggers apoptosis via induced liposaccharides [ 45 , 55 , 56 ]. In concert with miR-155, miR-146 downregulates expression of IRAK1 and TRAF6 , which are upstream activators of NF-κβ [ 5 ].…”
Section: Mirnas In Cardiomyocytesmentioning
confidence: 99%
“…IL-6 , along with NLRP3 , is mediated by miR-233 in monocytes [ 45 ]. Further, during myocarditis, miR-155 upregulates macrophages and CD4 + T lymphocytes [ 55 ]. Another strategic player during inflammation is miR-126, due to its control over endothelial VCAM-1 , which in turn help controls leukocyte trafficking and vasculature inflammation, potentially leading to cardiac repair by affecting the homing of hematopoietic progenitor cells [ 9 , 45 ].…”
Section: Mirnas In Cardiomyocytesmentioning
confidence: 99%
“…MiRNAs play a wide range of roles in regulating life activities through posttranscriptional inhibition. MiRNAs are involved in multiple biological processes including cell proliferation, differentiation, and metabolism [13, 19, 29] by modulating specific genes. It has been shown that miRNAs are abnormally expressed in many types of diseases, including heart disease, inflammatory diseases, and especially cancers [20, 21, 30].…”
Section: Introductionmentioning
confidence: 99%
“…In murine systems, miR-155-3p has been shown to be upregulated in M1 (LPS and IFNγ) bone marrow-derived macrophages 15 , as well as in infiltrating T helper cells in experimental autoimmune encephalomyelitis 16 . As well as immune pathways, miR-155-3p has been reported to be regulated in other physiological process, including downregulation during cardiogenesis from embryonic stem cells 17 and in human glioblastoma cells during hypoxia 18 . It was also identified in a methylated form in mantle cell lymphoma (MCL; an aggressive B-cell non-Hodgkin's lymphoma), and demethylation resulted in increased expression, revealing tumour suppressing properties 19 .…”
Section: Introductionmentioning
confidence: 99%